1995
DOI: 10.3758/bf03206507
|View full text |Cite
|
Sign up to set email alerts
|

Temporal interval production and processing in working memory

Abstract: Short-term memory or working memory has been proposed as a cognitive structure contributing to time estimation. Thus, in a previous experiment, retrieving a stored item during a temporalinterval production lengthened the interval in proportion to the number of items in the memory set. In the present study, this issue was analyzed further by testing whether the proportional lengthening is induced by the load itself (i.e., the number of items) or by comparing the probe with memorized items. In a first experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
111
2
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 27 publications
12
111
2
3
Order By: Relevance
“…This dissociation is in agreement [???? ] with previous results showing an absence of interference from maintenance of information in memory on concurrent timing with other memory tasks (Field & Groeger, 2004;Fortin & Breton, 1995;Fortin & Massé, 1999;Rammsayer & Ulrich, 2005) but shows that maintenance of temporal order may have some effect on timing. timing and concurrent tasks in terms of specialized resources (Wickens, 1984(Wickens, , 1992 or memory subsystems (Baddeley, 1986;Baddeley, 2000;Baddeley & Hitch, 1974) as proposed by Brown (1997).…”
Section: Temporal Productionssupporting
confidence: 56%
See 1 more Smart Citation
“…This dissociation is in agreement [???? ] with previous results showing an absence of interference from maintenance of information in memory on concurrent timing with other memory tasks (Field & Groeger, 2004;Fortin & Breton, 1995;Fortin & Massé, 1999;Rammsayer & Ulrich, 2005) but shows that maintenance of temporal order may have some effect on timing. timing and concurrent tasks in terms of specialized resources (Wickens, 1984(Wickens, , 1992 or memory subsystems (Baddeley, 1986;Baddeley, 2000;Baddeley & Hitch, 1974) as proposed by Brown (1997).…”
Section: Temporal Productionssupporting
confidence: 56%
“…Memory processing often perturbs concurrent timing but there is usually no such effect with maintenance of information in memory (Field & Groeger, 2004;Fortin & Breton, 1995;Fortin & Massé, 1999;Rammsayer & Ulrich, 2005). However, produced intervals were lengthened by increasing the number of tone durations to remember during an interval production, which was considered to be caused by both tasks requiring remembering temporal information (Field & Groeger,Exp.…”
Section: Methodsmentioning
confidence: 99%
“…As has been proposed by Brown (1997) and Fortin and Breton (1995), attention allocation models of time estimation, including the attentional gate model, may benefit from connections being forged to the flourishing field of working memory research. This may help to further specify the cognitive processes addressed by the metaphor of directing attention to time.…”
Section: Discussionmentioning
confidence: 99%
“…Fortin, Rousseau, Bourque, and Kirouac (1993), for example, found that a search task demanding a high level of attention interfered with time production performance only if the search task had to be processed in shortterm memory. More precisely, Fortin and Breton (1995) showed that demands on the processing component, rather than the storage component, of working memory affected time production. Both studies indicate that some kinds of demands on working memory affect time production, whereas others do not.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is now commonly agreed that there is no such single, dedicated locus in the human brain, it is assumed that some sort of general-purpose, cognitively controlled internal clock mechanism is available for keeping track of time (Allman et al, 2014). This timekeeper hypothesis is supported by research showing that an additional cognitive task interferes with the production of regularly timed intervals (Brown, 1997;Fortin & Breton, 1995;Krampe, Doumas, Lavrysen, & Rapp, 2010;Ogden, Salominaite, Jones, Fisk, & Montgomery, 2011;Rattat, 2010). However, because the computational and cognitive resources of humans are limited, and temporal production often occurs in situations of cognitive load, the timekeeper hypothesis is presumably inadequate to fully explain timing behavior.…”
mentioning
confidence: 99%